Predicting the ideal apex of lumbar lordosis based on individual pelvic incidence and inflection point in asymptomatic adults - Wang, Jingyu; Zhang, Qianshi; Liu, Fubing; Yuan, Hui; Zhang, Yi; Wang, Xiaobin; Li, Jing (Frontiers in Surgery, 2022)
Abstract Objective: The main aim of this study was to comprehensively explore the relationship among pelvic incidence (PI), inflection point (IP), and apex of lumbar lordosis (LLA), and establish a predictive formula for LLA based on individual PI and IP in asymptomatic Chinese adults. Methods: A total of 385 asymptomatic adults with average age 38.3±11.9 years (range 20-73 years) were recruited between November, 2020 and October, 2021. Full-spine, standing X-rays were then obtained from each participant. Next, the following sagittal parameters were measured: PI, IP, LLA, the horizontal offset between the plumb line of the lumbar apex and that of the posterosuperior corner of S1 (LASO), the upper lumbar lordosis (ULL) and lower lumbar lordosis (LLL), lumbar lordosis (LL), and thoracic kyphosis (TK). Moreover, the association among PI, IP, and the other sagittal parameters was evaluated, followed by linear regression analyses. A p-value of < 0.05 was considered statistically significant. Results: PI showed statistically significant correlations with LLA (rs = -0.629; P＜0.01), LASO (rs = 0.537; P＜0.01), LLL (rs =0.788; P＜0.01), and LL (rs = 0.663; P＜0.01). On the other hand, IP also showed statistically significant correlations with LLA (rs = 0.671; P＜0.01), LASO (rs = -0.493; P＜0.01), LLL (rs = -0.402; P＜0.01), and LL (rs =-0.283; P＜0.01). The corresponding predictive formulae were displayed as follows: LLA=-0.03*PI+0.23*IP+14.45(R2=0.669); LASO=0.38*PI-2.09*IP+53.62(R2=0.460); and LLL=0.58*PI-0.88*IP+18.86 (R2=0.659). Conclusion: The specific lumbar shape should be modulated by pelvic morphology and IP level. In addition, we established predictive formulae for ideal sagittal lumbar profile based on individual PI and IP, with the overarching goal of helping surgeons to better comprehend the regulatory mechanisms of the individual sagittal lumbar alignment, and design a precise and personalized corrective plan.